Managerial Overconfidence and Accounting Conservatism - Manijeh Ramsheh (Shahid Bahonar University of Kerman, 2014)
Overconfident managers overestimate future returns from their firms’ investments. Thus, it is predicted that overconfident managers will tend to delay loss recognition and generally use less conservative accounting. This paper is concerned with the relationship between Accounting Conservatism and Managerial Overconfidence, and the effects of external monitoring on this relationship. The sample contains 62 firms over the period 1378–1391. The results indicate a negative relationship between managerial overconfidence and both the conditional and unconditional conservatism. In addition, the result provides evidence that external monitoring appears to mitigate the negative effect of overconfidence on conditional conservatism, but does not appear to have the same effect on unconditional conservatism.